An outbreak of leaf spot caused by Stemphylium solani on eggplant in Malaysia. - Nasehi, Abbas; Kadir, Jugah; Esfahani, Mehdi Nasr; Mahmodi, Farshid; Ghadirian, Hajar; Ashtiani, Farnaz Abed; Golkhandan, Elham (American Phytopathological Society, 2013)
In 2011, a severe gray leaf spot was observed on aubergine (Solanum melongena) in major aubergine growing areas in Malaysia, including the Pahang, Johor and Selangor states. Disease incidence was >70% in severely infected areas of approximately 150 ha of aubergine greenhouses and fields examined. Symptoms initially appeared as small (1-5 mm in diameter), brownish-black specks with concentric circles on the lower leaves. The specks then coalesced and developed into greyish-brown, necrotic lesions, which also appeared on the upper leaves. Eventually, the leaves senesced and were shed. Fungal colonies were greyish green to light brown, and produced a yellow pigment. Single, muriform, brown, oblong conidia formed at the terminal end of each conidiophore. The conidiophores were tan to light brown and ≤220 µm long. Based on these morphological criteria, 25 isolates of the fungus were identified as Stemphylium solani. Further confirmation of the identification was obtained by molecular characterization. A BLAST search in the NCBI database revealed that the sequence was 99% identical with published ITS sequences for two isolates of Stemphylium solani (Accession Nos. AF203451 and HQ840713). This is thought to be the first report of Stemphylium solani on aubergine in Malaysia.